Dopamine receptor D2 inhibition alleviates diabetic hepatic stellate cells fibrosis by regulating the TGF‐β1/Smads and NFκB pathways. (26th November 2020) - Zhao, Bingbing; Li, Siwei; Guo, Zuoming; Chen, Zhe; Zhang, Xinying; Xu, Changqing; Chen, Junting; Wei, Can
Abstract: Diabetic hepatic fibrosis (DHF) is a progressive liver disease and a chronic complication of diabetes mellitus. The main cause of DHF is the activation of quiescent hepatic stellate cells (HSCs) by high glucose stimulation. Dopamine receptor D2 (DRD2)‐mediated dopamine signalling can be involved in the regulation of diabetic liver disease, but the exact role of DRD2 in DHF is still poorly understood. This study aimed to investigate the protective effect of DRD2 inhibition on diabetic liver fibrosis and the potential mechanism. We established both streptozotocin (STZ)‐induced type 1 diabetes (T1D, fed for 20 weeks) rat model and high glucose (HG, 40 mmol/L)‐stimulated HSCs model. The results from both the rats with STZ and the HSCs treated with HG showed increased expression of DRD2, NOX‐5, inflammation‐related proteins (IL‐6 and TNFα) and fibrosis‐related proteins (TGF‐β1, CO‐Ⅰ/Ⅲ/ IV, MMP‐2/9 and fibronectin). In vivo, the serum aspartate aminotransferase (AST), alanine aminotransferase (ALT) and total antioxidant capacity (T‐AOC) levels were significantly increased, and hematoxylin‐eosin (HE) staining, Masson staining, and electron microscopy revealed liver lesions and hepatocyte injury. In addition, HG‐treated HSCs exhibited altered oxidative stress ‐ related indexes, including superoxide dismutase (SOD), malondialdehyde (MDA) and reactive oxygen species (ROS), changed and abnormally proliferated in vitro. TGF‐β1, the phosphorylated Smad2, nuclear NFκB‐p65, phosphorylated NFκB‐p65 and phosphorylated IκBα were also increased. Interestingly, haloperidol (DRD2 inhibitor) and n‐acetyl‐L‐cysteine (NAC, an active oxygen scavenger) reduced the above‐mentioned changes. In conclusion, DRD2 inhibition can reduce diabetic HSCs oxidative damage and fibrotic proliferation partly via the TGF‐β1/Smads and NFκB pathways. Abstract : In summary, we demonstrated that DRD2 was up‐regulated in diabetic livers and HG‐treated HSCs, and then subsequently triggered oxidative stress and the inflammatory response, eventually resulting in hepatic fibrosis. DRD2 inhibition mainly attenuated HG‐stimulated HSCs activation and oxidative and inflammatory injury by inhibiting the TGF‐β1/Smads and NFκB pathways. This study investigated the potential mechanisms by which DRD2 inhibition products against oxidative damage due to DHF, which may provide new therapeutic targets for antioxidant treatments for DHF.